(untitled) (The Pakistan Development Review, 2006)
The study develops a formulation to decompose variability in profit into price and production effects. The production effect is further segregated into management and weather effects. The formulation is used to compare and decompose risk in the profit of three existing cropping patterns (corn-corn, corn-fallow, and rice-fallow) in the rainfed areas of Claveria, northern Mindanao, Philippines. High variability and low profitability of the crops in a more risky season (dry in our case) can limit cropping intensities in rainfed areas. However, intensification of the crops during the less risky season (wet in our case) can provide the necessary stake to invest in the risky season crops. Although weather is the dominant factor in explaining total variability, this should not be interpreted as a general rule for all agricultural environments. In an environment where input intensity is high, and input-output markets are inefficient, management and price effects can dominate the weather effect. JEL classification: Q12 Keywords: Cropping Pattern, Weather Risk, Management Risk, Price Risk, Profit, Expected Utility